2008
DOI: 10.1016/j.carres.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

GM3, GM2 and GM1 mimics designed for biosensing: chemoenzymatic synthesis, target affinities and 900MHz NMR analysis

Abstract: Abstract-Undec-10-enyl, undec-10-ynyl and 11-azidoundecyl glycoside analogues corresponding to the oligosaccharides of human gangliosides GM3, GM2 and GM1 were synthesized in high yields using glycosyltransferases from Campylobacter jejuni. Due to poor water solubility of the substrates, the reactions were carried out in methanol-water media, which for the first time were shown to be compatible with the C. jejuni a-(2?3)-sialyltransferase (CST-06) and b-(1?4)-N-acetylgalactosaminyltransferase (CJL-30). Bioequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 72 publications
0
35
0
Order By: Relevance
“…[10] IC 50 values were found to be four to five orders of magnitude lower than those for monovalent GM1 derivative GM1-1. [24] In the present study we found that these compounds are also active against the B-pentamer of E. coli heat-labile toxin (LTBh) which has identical GM1 binding sites to CTB. [25] Although there are subtle differences in the binding affinities of CTB and LTB isoforms for a range of ligands, [26] CTB and LTB are often used interchangeably when testing inhibitors.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[10] IC 50 values were found to be four to five orders of magnitude lower than those for monovalent GM1 derivative GM1-1. [24] In the present study we found that these compounds are also active against the B-pentamer of E. coli heat-labile toxin (LTBh) which has identical GM1 binding sites to CTB. [25] Although there are subtle differences in the binding affinities of CTB and LTB isoforms for a range of ligands, [26] CTB and LTB are often used interchangeably when testing inhibitors.…”
Section: Resultsmentioning
confidence: 94%
“…[32,[41][42][43] Experimental Section Sample preparation: Compounds GM1-1, GM1-2 and GM1-4 were prepared as reported previously. [10,24] Buffers and other reagents were bought from Sigma or Fisher unless stated otherwise.…”
Section: Resultsmentioning
confidence: 99%
“…[13] The GM1os ligand was prepared by first synthesizing Bocprotected aminooxy alkyne 3 (Scheme 1) according to a reported procedure. [14] GM1 azide 2 was prepared using a chemo-enzymatic approach [15] before ligation to aminooxy alkyne 3 employing a copper-catalyzed alkyne azide cycloaddition (CuAAC) at room temperature with stirring for 48 hours. Attempts were made to use microwave-assisted CuAAC for the synthesis, [16] but proved unsuccessful in this case.…”
mentioning
confidence: 99%
“…CMP-Neu5Gc was synthesized from Neu5Gc and CTP using the recombinant CMP-Neu5Ac synthetase (construct NSY-05) from Neisseria meningitidis (40). 3GSLN was synthesized from CMP-Neu5Gc and N-acetyllactosamine using the recombinant Cst-I ␣-2,3-sialyltransferase (construct CST-06) from Campylobacter jejuni (41). The synthesized 3GSLN was purified by size exclusion chromatography on a Superdex peptide column (10 mm by 30 cm; GE Healthcare) using 20 mM NH 4 CO 3 as the eluent.…”
Section: Methodsmentioning
confidence: 99%